Desk review report on agrobiodiversity, agroecology/nature-positive practices, and circular economy in Vietnam - Pham, Tho Thi Hanh (2022)
The development of Vietnam's agriculture and rural areas in the period from now to 2030 is of particular interest to the Party and the State of Vietnam, determined in the direction of restructuring agriculture towards ecology, modern agriculture, and transforming thinking. agricultural production, linking agricultural production with industry and services, production with preservation, processing, consumption, and enhancement of the value chain (Resolution of the XIII Party Congress). Resolution No. 19-NQ/TW of the Fifth Conference of the 13th Central Committee of the Communist Party on Agriculture, Farmers and Rural to 2030, with a vision to 2045 identifies the goal of fast-growing agriculture, effectively, sustainably, ensuring national food security, protecting the ecological environment and adapt to climate change through the tasks of restructuring agriculture substantively and effectively, taking advantage of which prioritizes the restructuring of crops and livestock to meet the needs of domestic and export markets, actively integrating and expanding the market. Therefore, Vietnam is trying to encourage finding solutions and scaling up initiatives to achieve this direction. The "National Action Plan - NAP" to transform the Food System towards transparency, responsible and sustainability till 2030 is finalizing and submitting to the Prime Minister for Approval. To support this NAP approval, a technical report is required. The Nature+ project is one of the important Initiatives to re-imagine, co-create, and implement nature-positive solutions-based agrifood systems that equitably support local food and livelihoods, while simultaneously ensuring that agriculture is a net positive contributor to nature. To contribute to the NAP technical report, the project implemented a review of related fields, including: - The current situation of agrobiodiversity in Vietnam - The current situation of agroecology/nature-positive practices in Vietnam - The current situation of the circular economy in Vietnam - The status of the use of input in Vietnam to improve food safety in Vietnam The reviewed outputs are not only contributing to the NAP report but also providing knowledge of several strategic policies in Vietnam such as Strategy for sustainable agricultural and rural development from 2021 to 2030 and a vision for 2050 (Decision 150/QD-TTg dated January 28, 2022); Decree 06/2022/ND-CP regulating GHG emission reduction and ozone layer protection; National plan to adapt to climate change for the period of 2021-2030, with a vision to 2050 (Decision 1055/QD-TTg dated July 20, 2020); National strategy on green growth for the period of 2021 - 2030, with a vision to 2050 (Decision 1658/QD-TTg dated October 1, 2021); Project on Development of Circular Economy in Vietnam (Decision No. 687/QD-TTg dated June 7, 2022).